2001
DOI: 10.1182/blood.v97.4.835
|View full text |Cite
|
Sign up to set email alerts
|

An Epstein-Barr virus deletion mutant associated with fatal lymphoproliferative disease unresponsive to therapy with virus-specific CTLs

Abstract: There is a growing interest in using antigen-specific T cells for the treatment of human malignancy. For example, adoptive transfer of Epstein-Barr virus (EBV)-specific cytotoxic T lymphocytes (CTLs) has been effective prophylaxis and treatment of EBV-associated lymphoproliferative disease in immunocompromised patients. For all immunotherapies, however, there has been a hypothetical concern that mutations in tumor-specific antigens may lead to tumor escape. We now demonstrate that such events may indeed occur,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
161
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(168 citation statements)
references
References 55 publications
(75 reference statements)
3
161
0
2
Order By: Relevance
“…This difference is likely due in part to the strength of the immune selection in our model system, in which all the preexisting CD8 T cells were specific to OVA. Consistent with this idea, a 245-bp deletion that eliminated two immunodominant epitopes was observed in the EBV mutant virus from the patient with lymphoproliferative disease who received EBVspecific CTLs as adoptive immunotherapy (10). Additionally, the immune selection in our model system was against an exogenous protein that had no function for the virus and was therefore completely dispensable.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…This difference is likely due in part to the strength of the immune selection in our model system, in which all the preexisting CD8 T cells were specific to OVA. Consistent with this idea, a 245-bp deletion that eliminated two immunodominant epitopes was observed in the EBV mutant virus from the patient with lymphoproliferative disease who received EBVspecific CTLs as adoptive immunotherapy (10). Additionally, the immune selection in our model system was against an exogenous protein that had no function for the virus and was therefore completely dispensable.…”
supporting
confidence: 62%
“…A bone marrow transplant patient with Epstein-Barr virus (EBV)-associated lymphoproliferative disease who was treated with adoptively transferred EBV-specific cytotoxic T lymphocytes (CTLs) developed progressive disease and died. Tumor cells from this patient were found to be resistant to cytolysis by the EBV-specific CTLs, and sequence analysis revealed a mutation that deleted the two immunodominant epitopes recognized by the CTLs (10). Studies have also examined EBV sequence variations in human populations with differing prevalences of specific human leukocyte antigen (HLA) alleles.…”
mentioning
confidence: 99%
“…For immunosuppressed patients, it appears clear that T-cell deficiency favors appearance of latency III malignancies (3), that adoptive T-cell therapy can prevent this (4,5), and that T-cell therapy fails if the EBV strain in question does not express crucial CD8 + T-cell epitopes in a latency III protein (50). Regarding infection in immunocompetent carriers, there were early arguments against a T-cell surveillance of latency III (51), but later studies showed that latency III-associated CD8 + T-cell epitopes are in fact under a selective pressure that depends on the frequency of HLA class I allotypes in a population (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem examination of this patient's tumor revealed a deletion in the tumor virus antigen EBNA-3B, which altered the tumor's HLA-restricted epitopes and rendered it unresponsive to the donor CTL infusion, which was directed against the wild-type EBNA-3B epitope. 59 The mutated virus appeared to have originated in the recipient after transplant. This case report demonstrated the possibility of EBV 'escape mutants' and a potential limitation of this therapy.…”
Section: Cellular Immunotherapymentioning
confidence: 99%